The Wealth of religions: The political economy of believing and belonging - Mccleary, rachel M.; Barro, robert J. (New Jersey Princeton university press, 2019)
The Wealth of Religions, Rachel McCleary and Robert Barro draw on their long record of pioneering research to examine these and many other aspects of the economics of religion. Places with firm beliefs in heaven and hell measured relative to the time spent in religious activities tend to be more productive and experience faster growth.
Keywords: Economic development Religious aspects; Economics Religious aspects; Development economics Aspect